Are multimodals more likely to change their travel behaviour? A cross-sectional analysis to explore the theoretical link between multimodality and the intention to change mode choice. (July 2018) - Heinen, Eva
Highlights: Multimodality may be a predictor of behavioural change. We investigated whether it was associated with the intention to change mode choice. Our analyses revealed mostly non-significant, but intuitive associations. Multimodal individuals were more likely to intend to decrease their car use. Additional research will be necessary on multimodality and behavioural change. Abstract: Existing research suggests that being more multimodal (i.e. the use of more than one transport mode within a given period of time) increases the likelihood of changing travel behaviour over time. However, alternative explanations may have contributed to these findings. Many well-known psychological theories state that the actual demonstration of a behaviour is preceded by an intention to demonstrate this behaviour. Therefore, one essential step towards the determination of a causal relationship between multimodality and behaviour change is to investigate whether multimodality increases the intention to change. This paper explored to what extent multimodality was associated with the intention to change the level of cycling, walking, car use, and train use. Our findings showed that the more multimodal individuals were, the more likely they intended to decrease their car use. However, most associations between multimodality and the intention to change mode choice were non-significant. This could be interpreted to mean that there is no relationship between multimodality and the intention to change. However, the significant findings for car use, and the direction of most (non-significant) associations in our analyses were intuitive. Therefore, our analyses are not conclusive on whether or not the level of multimodality is associated with the intention to change and actual behavioural change. Additional research will be necessary to test the proposed link between multimodality and behavioural change. Three lines of additional research that focus on associations between multimodality and behavioural change, multimodality and the intention to change behaviour, and variability and stability of individual behaviour over time, respectively, are particularly important.